Bioactive Fraction of Mentha piperita Leaves Extract Stimulates Lipoprotein Lipase at Cellular and Molecular Levels via Augmentation of Antioxidant Defense System in Hyperlipidemic Rats. Issue 3 (3rd July 2021) - Mohammed, Hafsat Abdullahi; Sallau, Abdullahi Balarabe; Nzelibe, Humphrey Chukwu; Muhammad, Aliyu; Erukainure, Ochuko Lucky; Musa, Bashir; Anigo, Mathew Kola
ABSTRACT: The antihyperlipidemic and antioxidant effects of Mentha piperita leaves extracts in Poloxamer 407-induced hyperlipidemic rats were investigated. Antihyperlipidemic activities of hexane, ethyl acetate, and methanol extracts (100, 200, or 300 mg kg −1 b.w.) were evaluated by lipid profile analysis. Twelve (12) fractions (F1 to F12) were collected from the most antihyperlipidemic extract (ethyl acetate at 100 mg kg −1 ) and, assayed in vivo for antihyperlipidemic activity. The effects of the most antihyperlipidemic fraction (F2) on redox sensitive biomarkers (SOD, CAT, GSH, MDA) and lipoprotein lipase (LPL) activity at cellular and molecular levels were evaluated. Fraction-2 (F2) was further subjected to GC-MS and LC-MS analysis for identification of nonpolar and polar components. The F2 treatment decreased the level of MDA with concomitant enhancement of GSH, LPL activity in the liver and serum and up regulated the expression of SOD, CAT, and LPL genes in liver and blood relative to the untreated rats. GC-MS and LC-MS revealed oleic acid, vaccenic acid, 3, 4-dicaffeoylquinic acid, coumarin, and triacontane as the probable bioactive components with reported antihyperlipidemic and antioxidant effects.